1992
DOI: 10.1080/00103629209368666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sulfur and nitrogen fertilzer on the uptake of iron, manganese, and zinc by corn plants grown in calcareous soil

Abstract: A pot experiment was conducted with a coarse-textured calcareous soil (pH-H 2 O 8.3) to study the effect of single and combined application of N and S fertilizers on soil pH, Fe, Mn, Zn, and P mobilization, and on growth and micronutrient uptake by com (Zea mays L.). Increasing amounts of elemental sulfur were mixed with the soil. To stimulate S oxidation, the treated soils were incubated for six weeks at field capacity. Nitrogen was applied as NH 4 NO 3 (100, 200, and 400 mg N/kg). After six weeks, dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
1
14
1
2
Order By: Relevance
“…The soil pH dropped from an initial value of 9.08 to 7.56 by addition of S 0 and N fertilizer. In the present study, soil pH decreased more than 1.0 unit and our findings were the same with that of Soliman et al (1992) where a decrease of soil pH by 0.2, 0.5 and 0.9 units was reported as a result of increasing S applications.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The soil pH dropped from an initial value of 9.08 to 7.56 by addition of S 0 and N fertilizer. In the present study, soil pH decreased more than 1.0 unit and our findings were the same with that of Soliman et al (1992) where a decrease of soil pH by 0.2, 0.5 and 0.9 units was reported as a result of increasing S applications.…”
Section: Discussionsupporting
confidence: 80%
“…Application of higher levels of S 0 with N played significant role in respect of Mn uptake of maize plants. Manganese uptake was higher along with higher application of N which was most evident at higher S application rates (Kaya et al, 2009;Soliman et al, 1992). The results clearly showed that Zn and Mn uptake increased significantly by corn plants when grown with moderate levels of S 0 with N, whereas zero S 0 and N recorded poor uptake of Mn.…”
Section: Discussionmentioning
confidence: 59%
“…A healthy human diet must contain seven macrominerals (Na, K, Ca, Mg, S, P, Cl) and 17 microelements (Fe, Zn, Cu, Mn, I, F, B, Se, Mo, Ni, Cr, Si, As, Li, Sn, V, Co) (Welch and Graham 2004). These elements must be supplied through soil, including application of S and N (Soliman et al 1992) and Zn (Wijesundara et al 1991). There are several strategies for improving availability of macrominerals and microelements in soil.…”
Section: Enhancing Micronutrients In Soilmentioning
confidence: 98%
“…Soil organic matter and pH are the key factors affecting the content and mobility of heavy metals in soil (Soliman et al 1992, Martinez and Motto 2000, Borůvka and Drábek 2004, Šichorová et al 2004. Another important consideration is human activity which contributes to soil contamination in some regions of Poland, thus leading to changes in the natural heavy metals content.…”
mentioning
confidence: 99%